Quebrando as regras: o poder discricionário na linha de frente do programa esportivo-social RIO 2016 um estudo sobre a situação do integrador de núcleo, um verdadeiro 'sociological citizen' - Machado, Nivaldo Leitão (2013)
This study analyzes the individual working at the front of RIO 2016, a Rio de Janeiro Government social welfare program that operates 800 service centers in Rio de Janeiro state. T he State Department of Sport and Recreation of Rio de Janeiro is responsible for the implementation and management of this program . Th e focus of this research is the individual that plays the role of the Sport Center Integrator . The Integrator is responsible for the management of these Sports Center units. Each center serves an average of 50 students in a underprivileged community in Rio de Janeiro state . This research analyzes the Integrator under a n original perspective, understanding him as an agent that acts beyond the scope of his assigned tasks . T his study considered theories of organizational bureaucracy, making use of Michel Crozi er literature 'The Bureaucratic Phenomenon' (1964), which analyzes th e relationships between people, g roups and power to understand the influence of bureaucratic organization in the individual. The term 'sociological citizen' developed by Silbey (Silbey et al. 2009) was also considered to classify the individual who proves more enthusiastic than others in attending the organizational and legal mandate. Silbey also applies the term 'relational regulation' to describe this particular form of practice of 'soci ological cit izenship', through which the agents govern the gap between expectations and required performance. ' Integrators interviewed , or at least part of them, serve the population with a critical eye at the organizational rules, fact that draws attenti on to the issues of Flexible Bureaucracies, discussed by Michael Lipsky in the late 60s (Lipsky 1980) to designate hierarchical organizations wh ere agents of the front line, at the bottom of the hierarchy, have substantial discretion. Admittedly , Lipsky fo cused more on the functions that naturally have this discretion granted by organizational hierarchy, such as sheriffs , police man and social workers. In our case, we are faced with someone working at the lowest level of the hierarchy, without formal delegat ion of power but with responsibility to manage an operational unit of the public service - the Sports Center. Therefore this study analyzes the bureaucratic actor behavior - Integrator - in their duties of managing the operation of sports activities conduc ted by physical education teachers to the students when he is subjected to the rules and procedures established by the program managers - members of the Department of Sport and Recreation State of Rio de Janeiro Government. The Sports Center s are located i n underserved communities in the state of Rio de Janeiro, including those who received the Pacifying Police Units - UPP in the state capital, and present socio economic and cultural factors that vary from one community to another. The reality peculiarities in each community require that the actions and decisions taken by the Integrator do not always follow the rules , but usually the decisions and actions are effective in their final results considering the environmental conditions when decision was taken . I n addition to public and received document analysis, this study included interviews with key players on both sides of the program, the state government managers and integrators of Sports Center. The result showed that despite the rules placed by the progra m being frequently pushed aside by the agents, the final results of the program are considered positive and promising by managers. Thus, this study contributes to the formulators of public policies who establish rules for agents t hat operate at 'Street Lev el' (Lipsky 1980) . Results presented here give formulators an incentive to focus their efforts on setting goals to be achieved by agents rather than establishing rigid and inflexible procedures for individuals faced with dynamic situations involving direct contact with people. The literary contribution of this work lies in the observation of applying these concepts in a social - sports program that is considered by m anagers as the state government greatest capillarity social program, enforced by the singular moment of major sporting events including the FIFA W orld Cup 2014 and Olympics 2016 programmed to Rio de Janeiro.